1994
DOI: 10.1073/pnas.91.12.5612
|View full text |Cite
|
Sign up to set email alerts
|

Anti-peptidyl transferase leader peptides of attenuation-regulated chloramphenicol-resistance genes.

Abstract: The chloramphenicol (Cm)-inducible emL4 gene of Tn1696 specifies nonenzymatic resistance to Cm and is regulated by attenuation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
67
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(70 citation statements)
references
References 32 publications
3
67
0
Order By: Relevance
“…For instance, regulatory peptides encoded by leader regions of genes for resistance determinants against some antibiotics, such as erythromycin and chloramphenicol, undergo antibiotic-induced elongation arrest both in Gram-positive and Gram-negative bacteria (3,21,22). Clusters of positively charged amino acids can cause arrest in translation in eukaryotic ribosomes (23).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, regulatory peptides encoded by leader regions of genes for resistance determinants against some antibiotics, such as erythromycin and chloramphenicol, undergo antibiotic-induced elongation arrest both in Gram-positive and Gram-negative bacteria (3,21,22). Clusters of positively charged amino acids can cause arrest in translation in eukaryotic ribosomes (23).…”
Section: Discussionmentioning
confidence: 99%
“…Members of both classes of peptides may function similarly on the basis of their common footprints on 23S rRNA and the sensitivity of the inhibitory activity to competition by erythromycin (10). The mechanism of peptide inhibition of PT is probably not identical to that of chloramphenicol since the activities of chloramphenicol and the peptides are additive (10).The anti-PT activity of the leader peptides is thought to play a critical role in the translation attenuation regulation of cat (1,8,11,13,17,26) and cmlA (6,33) by selecting the site of ribosome stalling (10,12). Thus, the in vivo synthesis of the inhibitor peptides coincides with the translation by a ribosome to the leader site at which ribosome stalling will activate downstream gene expression (1, 10).…”
mentioning
confidence: 99%
“…We have recently demonstrated that PT is also inhibited by the short peptides that are encoded by the leaders of attenuation regulated. chloramphenicol resistance genes (10,12). The peptide inhibitors fall into two classes according to their sizes and specific inhibition.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in both eukaryotes and prokaryotes have demonstrated that uORF peptides can cause ribosomal stalling by various mechanisms, including interference with the peptidyl transferase center activity (Gu et al 1994;Lovett and Rogers 1996), thereby inhibiting translation termination by preventing peptidyl-tRNA hydrolysis (Janzen et al 2002) or by causing arrest of elongating or terminating ribosomes in response to a cellular signal (Luo et al 1995;Wang and Sachs 1997;Hood et al 2009). It is also noteworthy that studies have implicated the role of highly basic peptides in impeding translation, possibly by causing conformational changes in rRNA (Lovett and Rogers 1996).…”
Section: Discussionmentioning
confidence: 99%